Women, intersectionality, and power in group psychotherapy leadership - Kane, Yoon Im; Masselink, Saralyn M.; Weiss, Annie C. (New York, NY : Routledge, 2022)
"This ground-breaking book presents multifaceted perspectives of women group psychotherapy leaders to examines embedded assumptions about gender, intersecting identities, and power that impact women's perspectives as group psychotherapists, mentors, and educators. Integrating a range of theoretical, clinical, and experiential material, chapters critically examine philosophical, cultural, and personal paradigms to challenge societally embedded norms regarding leadership identity, caretaking and authority and encourage deeper gender and cultural intelligence among psychotherapy group leaders. Contributing authors discuss the personal experience, theories, training, mentorship, and clinical work that has supported their leadership. Explored themes include, intersectionality, gender-role identity, hidden biases, and the challenge of maintaining a stance that is nurturing and empathic, yet robust enough to manage boundaries, and handle aggression. The text offer guidance and clinical wisdom which will inspire, scaffold, and embolden all psychotherapy group leaders"--
Keywords: Women psychotherapists; Group psychotherapy; Leadership in women; Intersectionality (Sociology); Sex role; PSYCHOLOGY / Psychotherapy / Group; SOCIAL SCIENCE / Gender Studies